Reconstruction of The Pawn Agreement Based on Justice - Budi Wasana; Krisnadi Nasution; Rosalinda Elsina Latumahina (Batulis Civil Law Review)
Introduction: Legally, the clauses in the pawn agreement still contain clauses that conflict with the Consumer Protection Law Nomor 8 of 1999 Article 18 paragraph (1) letter a which states that business actors who offer goods and/or services intended for trading are prohibited from making or including standard clauses in each document and/or agreement if: they state the transfer of responsibility of the business actor. In the pawn agreement there are still missing clauses that should be included in the pawn agreement.